2023
DOI: 10.1039/d3dt01656k
|View full text |Cite
|
Sign up to set email alerts
|

Design of N-heterocycle based-phthalonitrile/metal phthalocyanine–silver nanoconjugates for cancer therapies

Özlem İpsiz Öney,
H. Yasemin Yenilmez,
Dilek Bahar
et al.

Abstract: This study reports the anticancer properties of carbazole-containing phthalonitrile/phthalocyanine-modified silver nanoparticles for the first time. In this study, a new mono-substituted phthalonitrile namely 3-[9H-Carbazole-9-ethoxy]phthalonitrile and its metal phthalocyanines {M =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…The higher peak current and peak position of Oxd 1 indicated that this process arose from the oxidation of the carbazole substituent and cationic electropolymerization of compound 2 on the electrode surface. 37,68 After Oxd 2 , the redox responses of the oxidation processes completely changed during the consecutive CV scan owing to the electropolymerization of the compound on the electrode surface. The green electropolymerized film was easily observed with the naked eye.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher peak current and peak position of Oxd 1 indicated that this process arose from the oxidation of the carbazole substituent and cationic electropolymerization of compound 2 on the electrode surface. 37,68 After Oxd 2 , the redox responses of the oxidation processes completely changed during the consecutive CV scan owing to the electropolymerization of the compound on the electrode surface. The green electropolymerized film was easily observed with the naked eye.…”
Section: Paper Dalton Transactionsmentioning
confidence: 99%
“…Since the effects of carbazole groups on the chemical, physical, and optical properties of phthalocyanines have been rarely studied, our group has been interested in research on scientific features of novel carbazole-containing phthalocyanines in recent years. 37–40…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation